Field guide to case study research in tourism, hospitality and leisure - Hyde, Kenneth F.; Ryan, Chris, 1945-; Woodside, Arch G. (Advances in culture, tourism and hospitality research ;, 2012)
This field guide provides methods and studies on how-to-do case study research in natural settings. A truly international guide, this text is ideal for those studying and conducting case study research in tourism, hospitality and leisure disciplines. It provides a comprehensive and practical account of how to describe, explain and predict both individual and group case behavior, at the same time explaining behavior among a set of cases relevant to a specific context. This guide embraces and extends Herbert Simon's (Nobel Prize in Economics recipient) insight that a decision results from the conjoining two antecedents in human behavior: cognitive processing of an individual or group and a given context or problem framing. Divided into six parts, this guide includes chapters on: analysis of texts; how-to-do executive interviews; field interviewing in international contexts; stakeholder participatory research; researching indigenous and marginal peoples; and cross-case analysis. The chapters increase skills and understanding of culture, tourism, and hospitality behavior through analysis of the four principle objectives of case study research: accomplishing accuracy; achieving generality; reporting complexity and broad coverage; and achieving impact for improving the individual condition, client, and/or society.